Simulation of flow around bluff bodies and bridge deck sections using CFD - Liaw, Kai (2005)
This thesis focuses on the simulation of flow around bluff bodies and bridge deck sections, in which unsteady nature and vortex shedding of flow are commonly found, using computational fluid dynamics (CFD). Various turbulence models have been tested to develop understanding and proper modelling techniques for the flow around such bodies. Throughout the thesis, the turbulence models employed, mainly large eddy simulation (LES) and detached eddy simulation (DES), have been validated through comparative study with experimental work. The major part of the work discusses flow around bluff bodies ranging from a simple circular cylinder, a square cylinder to rectangular sections with various aspect ratios (1:2 to 1:8). The research section concentrates on modelling flow characteristics around bluff bodies to investigate the impact of fluid flow on them. This aids in the understanding of a more complex flow around bridge deck sections. The thesis combines investigation and discussion of the vortex shedding nature on the flow around bluff bodies, in which the simulations are done using advanced modelling techniques on high performance computing system. Work also includes a sectional wind tunnel test of the bridge deck section for the comparative study with the numerical solution. Finally, the conclusions outline the achievements and findings of the work done in this thesis and give recommendations for further research on the topic.